Drivers Of Purchase Intention And Willingness To Pay Microtransactions In Mobile Legends - Wilson James Metasurya Loa; Margaretha Pink Berlianto (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
This study aims to analyze the antecedents of satisfaction and continued use intention and investigate the effects of satisfaction and continued use intention towards Indonesian Mobile Legends players purchase intention and willingness to purchase for microtransactions. The population of this study was Indonesians who has played and purchased virtual items in Mobile Legends by distributing questionnaires to a total of 235 respondents. The sampling technique was purposive sampling. Data was analyzed using PLS-SEM. The results explored the influence of, social value, quality, and economic value having a positive impact on satisfaction and continued use intention except for social value that showed no effect on continued use intention. Satisfaction also influenced continued use intention and willingness to pay while continued use intention affected purchase intention. This study has succeeded in contributing towards research on the variables that influence satisfaction, continued use intention, purchase intention, and willingness to pay.